Development Strategy For Palm Sugar (Arenga Pinnata) - Aidah, Yuyu; Novita, Ita; Masithoh, Siti (Universitas Djuanda, 2024)
This study aims to determine the characteristics of palm sugar farmers and artisans, identify the internal and external factors affecting palm sugar development, and propose alternative development strategies for palm sugar in Sukamulya Village, Cikembar District, Sukabumi Regency. The selection of this location was purposive, considering that Sukamulya Village is a palm sugar-producing village. The research was conducted in April-May 2023. The analytical methods used in this study included the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Internal-External (IE) matrix, and SWOT matrix. Respondents were determined through a census, with a total of 20 respondents being palm sugar farmers and artisans in Sukamulya Village. The results of the IFE matrix assessment obtained a total score of 2.45, the EFE matrix obtained a total score of 2.58, and the IE matrix was in cell (V) (hold and maintain). Product development can be achieved through product diversification and innovation. From the assessment of the SWOT matrix analysis, 7 alternative marketing strategies were identified for palm sugar farmers and artisans in Sukamulya Village, Cikembar District, Sukabumi Regency.